2018
DOI: 10.1016/j.kint.2018.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Excessive neutrophil extracellular trap formation in ANCA-associated vasculitis is independent of ANCA

Abstract: Neutrophil extracellular traps (NETs) are auto-antigenic strands of extracellular DNA covered with myeloperoxidase (MPO) and proteinase3 (PR3) that can be a source for the formation of anti-neutrophil cytoplasmic autoantibodies (ANCAs). The presence of NETs was recently demonstrated in renal tissue of patients with ANCA-associated vasculitis (AAV). NET formation was enhanced in AAV, suggesting that MPO-ANCA could trigger NET formation, supporting a vicious circle placing NETs in the center of AAV pathogenesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 38 publications
8
59
0
3
Order By: Relevance
“…Recently, our group demonstrated that AAV‐induced NET formation occurred in a manner independent of IgG ANCAs , whereas SLE‐specific autoantibodies were reported to induce NET formation . We therefore further corroborated the involvement of autoantibodies in a direct comparison of AAV‐induced and SLE‐induced NET formation.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Recently, our group demonstrated that AAV‐induced NET formation occurred in a manner independent of IgG ANCAs , whereas SLE‐specific autoantibodies were reported to induce NET formation . We therefore further corroborated the involvement of autoantibodies in a direct comparison of AAV‐induced and SLE‐induced NET formation.…”
Section: Resultssupporting
confidence: 78%
“…Even though we demonstrated that AAV‐induced NET formation was independent of IgG ANCAs, the exact factors in AAV serum that trigger NET formation remain unknown. In a previous study, our group showed that neither IgA depletion nor C5 blockade affected AAV‐induced NET formation, and there was no correlation with the serum levels of tumor necrosis factor (TNF), interleukin‐8, or C‐reactive protein . Interestingly, the necroptosis pathway was recently demonstrated to be involved in ANCA‐mediated NET formation .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Similarly, druginduced formation of NETs enriched in NE serving as auto-antigen, together with the release of B-cell activating factor (BAFF) resulting in B-cell activation, and the production of ANCA directed against NE that further enhance NET formation, have been assumed to be pathogenic mechanisms in cocaine and levamisoleassociated autoimmunity 84 . A role for NETs in ANCAassociated vasculitis is also suggested by the observation that excessive NET formation correlated with disease exacerbation 85 .…”
Section: Nets In Vasculitis Rheumatoid Arthritis and Psoriasismentioning
confidence: 97%